Delivery of microRNA-126 by apoptotic bodies induces CXCL12-dependent vascular protection - Zernecke, Alma; Bidzhekov, Kiril; Noels, Heidi; Shagdarsuren, Erdenechimeg; Gan, Lin; Denecke, Bernd; Hristov, Mihail; Köppel, Thomas; Jahantigh, Maliheh Nazari; Lutgens, Esther; Wang, Shusheng; Olson, Eric N; et al. (Science signaling, 2009)
Apoptosis is a pivotal process in embryogenesis and postnatal cell homeostasis and involves the shedding of membranous microvesicles termed apoptotic bodies. In response to tissue damage, the CXC chemokine CXCL12 and its receptor CXCR4 counteract apoptosis and recruit progenitor cells. Here, we show that endothelial cell-derived apoptotic bodies are generated during atherosclerosis and convey paracrine alarm signals to recipient vascular cells that trigger the production of CXCL12. CXCL12 production was mediated by microRNA-126 (miR-126), which was enriched in apoptotic bodies and repressed the function of regulator of G protein (heterotrimeric guanosine triphosphate-binding protein) signaling 16, an inhibitor of G protein-coupled receptor (GPCR) signaling. This enabled CXCR4, a GPCR, to trigger an autoregulatory feedback loop that increased the production of CXCL12. Administration of apoptotic bodies or miR-126 limited atherosclerosis, promoted the incorporation of Sca-1+ progenitor cells, and conferred features of plaque stability on different mouse models of atherosclerosis. This study highlights functions of microRNAs in health and disease that may extend to the recruitment of progenitor cells during other forms of tissue repair or homeostasis.